Secured Compression for 2D Medical Images Through the Manifold and Fuzzy Trapezoidal Correlation Function - Parvathaneni Naga SRINIVASU; Norita Md Norwawi; Shanmuk Srinivas AMIRIPALLI; P. DEEPALAKSHMI (Gazi University, 2024)
Indexed by WOS/ Scopus